A Network Theory View on the Thalamo-Cortical Loop - Bakouie, F.; Gharibzadeh, S.; Towhidkhah, F. (Нейрофизиология, 2014)
We used a network theory approach, based on the dynamic core hypothesis (DCH), to study
the thalamo-cortical loop (TCL) and its subsets regarding their role in consciousness. We
used the Collation of Connectivity Data on the Macaque Brain (CoCoMac) and calculated the
degree distributions, transmission coefficients, connection density, clustering coefficients,
path lengths, and modularity. Our results showed that the TCL and cortex exhibit exponential
degree distributions, and the ratio of efferent/afferent connections in the thalamus is smaller
than 1.0 This may support the notion that the connections received by the thalamus from
the cortex play a key role in improving information processing in the conscious states. The
average values of transmission coefficients for the cortex and TCL were found to be equal to
1.49 and 1.28, respectively. This indicates that: (i) the cortex is a system that mainly transmits information outward rather than receives it; (ii) the TCL is a cooperative system that
performs this in a give-and-take manner; (iii) connections of the cortex are denser than those
in the TCL, showing that the cortex might be advantageous for processing of complicated
information during consciousness; (iv) both the TCL and cortex are small-world systems; (v)
the scaled value of the characteristic path length in the TCL is smaller than that in the cortex,
which implies a higher speed potential for information processing in the TCL than in the
cortex; (vi) the scaled value of the clustering coefficient is nearly the same in the cortex and
TCL, and (vii) the number of modules is 5 in the cortex and 6 in the TCL. Ми проаналізували організацію таламо-кортикальної петлі
(ТКП) і її компонентів, враховуючи її роль у забезпеченні
свідомості, з використанням підходу, заснованого на теорії мереж і гіпотезі динамічного ядра. Ми використали базу
даних про зв’язки в мозку макака (CoCoMac), розрахували
розподіли рівнів і значення коефіцієнтів передачі, щільності зв’язків, коефіцієнтів кластеризації, довжини зв’язків і
модальності. Отримані результати показали, що розподіли
рівнів для ТКП і кори є експоненціальними, а відношення кількостей еферентних та аферентних зв’язків у таламусі є меншим одиниці. Це підтверджує положення про те,
що зв’язки, одержані корою від таламуса, відіграють ключову роль в оптимізації обробки інформації в станах наявності свідомості. Середні значення коефіцієнтів передачі
для кори і ТКП дорівнювали 1.49 і 1.28 відповідно. Згідно
з цим, по-перше, кора є системою, котра в більшій мірі передає інформацію, ніж отримує її; по-друге, ТКП є кооперативною системою, яка виконує це в модусі „дай-та-бери”;
по-третє, зв’язки в корі є щільнішими, ніж у ТКП, що свідчить про провідну роль кори в обробці складної інформації
в стані свідомості; по-четверте, і ТКП, і кора є small-worldсистемами; по-п’яте, скалярне значення довжини зв’язків у
ТКП є меншим, ніж у корі, що вказує на потенційно більш
високу швидкість обробки інформації в ТКП, ніж у корі; пошосте, скалярні значення коефіцієнта кластеризації в ТКП і
корі є приблизно однаковими, і, по-сьоме, кількості модулів
у корі і ТКП відповідають п’яти і шести.